Analyzing Interpreting Strategy used by Low Proficiency EFL Students - Sakut Anshori; Yongki Ramadhan Putra; Prihantoro; Fahmi Gunawan (Script Journal: Journal of Linguistics and English Teaching, 2025)
Background: This study examines low-competency EFL students' first-time interpretation performance, concentrating on how they use their limited linguistic proficiency to interpret the messages. Student interpreters often face difficulties due to limited linguistic proficiency, which can result in misinterpretations in their first performance. However, there is currently a dearth of studies in this specific context.Methodology: Since how students use various techniques needs to be revealed in detail, their performances are recorded in the form of videos. Purposive sampling was used to select students who lacked fluency and interpreting experience. A corpus-assisted discourse analysis was applied to a dataset of 281 instances to identify recurring patterns in students' strategies. The analysis process was divided into two cycles to prevent data loss due to careless attention and insufficient reflection on human language patterns.Findings: Approximation was the most used strategy, occurring 46 times, followed by substitution at 38 instances, and compression appeared 30 times. Other strategies included reproduction (31 times), word-for-word translation (24 instances), and stalling (18 instances), with ten instances of omissions. The results further show that students keep having difficulty with vocabulary and general language transfer, which causes them to misinterpret messages. Nevertheless, students can achieve a balance between meaning loss and compression even with their insufficient language abilities in interpreting. A significant finding is the discovery of a new technique—cultural reference—that students employ to interpret utterances through cultural adaptation, which fundamentally alters how students interpret the language.Conclusion: This study concluded that students’ stronger cultural proficiency in one of their languages significantly affects their interpretation strategy. Students also frequently use wrong approximations to simplify complex information or manage time constraints while interpreting, leading to errors.Originality: The study's substantive findings clarify that inexperienced interpreters' strategies are influenced by cultural references, which contributes to fulfilling interpreting studies, particularly on first-time interpreting performance.